The zinc finger and BTB domain containing protein ZBTB20 regulates plasma triglyceride metabolism by repressing lipoprotein lipase gene transcription in hepatocytes. Issue 5 (1st December 2021) - Li, Hao; Liu, Gan; Wan, Xiaoqing; Zhou, Luting; Qin, Zhen‐Bang; Ma, Xian‐Hua; Su, Kai; Liu, Ya‐Jin; Yuan, Jinghao; Wei, Chun‐Chun; Ren, An‐Jing; Chen, Yu‐Xia; et al.
Abstract: Background and Aims: Lipoprotein lipase (LPL) is responsible for the lipolytic processing of triglyceride‐rich lipoproteins, the deficiency of which causes severe hypertriglyceridemia. Liver LPL expression is high in suckling rodents but relatively low at adulthood. However, the regulatory mechanism and functional significance of liver LPL expression are incompletely understood. We have established the zinc finger protein ZBTB20 as a critical factor for hepatic lipogenesis. Here, we evaluated the role of ZBTB20 in regulating liver Lpl gene transcription and plasma triglyceride metabolism. Approach and Results: Hepatocyte‐specific inactivation of ZBTB20 in mice led to a remarkable increase in LPL expression at the mRNA and protein levels in adult liver, in which LPL protein was mainly localized onto sinusoidal epithelial cells and Kupffer cells. As a result, the LPL activity in postheparin plasma was substantially increased, and postprandial plasma triglyceride clearance was significantly enhanced, whereas plasma triglyceride levels were decreased. The dysregulated liver LPL expression and low plasma triglyceride levels in ZBTB20‐deficient mice were normalized by inactivating hepatic LPL expression. ZBTB20 deficiency protected the mice against high‐fat diet–induced hyperlipidemia without causing excessive triglyceride accumulation in the liver. Chromatin immunoprecipitation and gel‐shift assay studies revealed that ZBTB20 binds to the LPL promoter in the liver. A luciferase reporter assay revealed that ZBTB20 inhibits the transcriptional activity of LPL promoter. The regulation of LPL expression by ZBTB20 is liver‐specific under physiological conditions. Conclusions: Liver ZBTB20 serves as a key regulator of LPL expression and plasma triglyceride metabolism and could be a therapeutic target for hypertriglyceridemia. Abstract : image